Hubungan Kekerabatan Ikan Kakatua (Scarus spp.) di Desa Labean Kabupaten Donggala Berdasarkan Karakter Morfologi - Kusumaningati, Lilis Tri; Budiarsa, I Made; Kundera, I Nengah; Ramadhan, Ahmad; Trianto, Manap; Jayanti, Zulaikhah Dwi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to describe the interspecies phylogenetic relationships of parrotfish (Scarus spp.) in Labean Village, Donggala Regency. The research employed an exploratory descriptive method conducted from October 2024 to March 2025. Samples were collected using a purposive sampling technique, with fishing lines and nets as the primary capture tools. The collected specimens were then identified and subjected to morphological measurements, including morphometric, meristic, and qualitative characters. Phylogenetic analysis was carried out using MVSP software with the simple matching coefficient method and UPGMA algorithm. The results revealed six identified parrotfish species: Scarus rivulatus, Scarus ovifrons, Scarus niger, Scarus tricolor, Scarus sordidus, and Scarus quoyi. Phylogenetic analysis indicated that Scarus rivulatus and Scarus quoyi exhibited the closest relationship (similarity index 0.912), whereas the most distant relationship was observed between node 4 and Scarus sordidus (similarity index 0.376). Morphological characters proved to be relatively stable in determining interspecies phylogenetic relationships among parrotfish. Therefore, the findings of this study are expected to contribute to parrotfish conservation efforts and serve as a reference for future research.